Композиційно-стилістична типологія англомовної новели - Сухова, Анна Вікторівна (Дрогобицький державний педагогічний університет ім. Івана Франка, 2016)
У статті досліджується композиція англомовної новели із застосуванням системно-структурного підходу. Особливу увагу приділено аналізу чотирьох композиційних рівнів художнього тексту: змістового, формального, формально-змістового та образно-символічного.

The article deals with the research of the Anglophone short story composition applying a systematic-structural approach. Special attention is drawn to the analysis of four compositional levels: content level, formal level, formal-content level and figurative-symbolic level. Each level of the composition has its own features. On the content level, the Anglophone short story is divided into such elements as exposition, rising action, development, climax and unexpected resolution. In accordance with the formal level, the Anglophone short story is composed of sentences, supra-phrasal units and fragments. The formal-content level includes architectonic and compositional speech forms. On the figurative-symbolic level, some short stories are characterized by the availability of certain symbolic images that can be static and dynamic. All these compositional aspects closely interact with and complement each other. From our point of view, the formal-content level is of the utmost interest, since it combines all the speech forms, that are part and parcel of the composition as a linguostylistic phenomenon. The analysis has shown that the text of the Anglophone short story consists mainly of author’s speech. Reported speech is represented in the form of direct, indirect and free indirect speech. The most widespread type of represented speech is direct one. Among main compositional speech forms there are narration, description and argumentation. The prevalent form is narration, which occurs in various combinations with description and argumentation. Therefore, we can draw a conclusion that there are several types of Anglophone short stories based on certain criteria.
Compositional-Stylistic Typology of the Anglophone Short Story
Keywords: композиція; англомовна новела; змістовий рівень; формальний рівень; формально-змістовий рівень; образно-символічний рівень; composition; Anglophone short story; content level; formal level; formal-content level; figurative-symbolic level